AN ERROR ANALYSIS OF WRITING RECOUNT TEXT BASED ON GENDER - Anggara, Yuda; Haryudin, Acep (IKIP Siliwangi, 2020)
in the recount text. Students errors were analyzed using errors analysis. This research used qualitative descriptive method as the research methodology. The data would be presented descriptively and the result was in explanation of words form which would be following by data presented in form of tables. The errors made by female there are 12 errors of omission, 13 errors in addition, 21 errors in misformation and 1 errors in misordering. while the errors are made by male there are 5 errors of omission, 5 errors in addition, 27 errors in misformation and 1 errors in misordering. The instrument in this research was a test item created by students. From this research it can be deduced that the most mistakes made by female and male are errors in the way of misformation because students lack understanding of how to make stories in the writing recount text. Keywords: Writing, Error Analysis, Recount text.